Implementasi Flipped Classroom Menggunakan Media Mind Mapping pada Asesmen Pembelajaran Kimia - Munawwarah M; Zulqifli Alqadri (Chemistry Education Department of Education and Teaching Faculty, 2022)
One of the learning models that is in line with the transition of the curriculum from teacher-centered to student-centered, namely the flipped classroom model. This study aims to determine the effect of the flipped classroom model with mind mapping media on student learning outcomes in the chemistry learning assessment subject. The type of research used is quasi-experimental with a control-group post test only design. The research sample is chemistry education students in the fifth semester. A total of 33 students in the experimental class and 33 students in the control class. The experimental class uses the flipped classroom model with Mind mapping media. The control class uses a direct learning model with the discussion method. The instrument used is in the form of essay questions on the Mid Semester Examination and the Final Semester Examination. The data obtained were analyzed by Independent sample t-test using Microsoft Excel. The results obtained are t-stat > t-critical (t-stat = 4.29, t-critical = 1.67). The results of the analysis show that students who go through the learning process using the flipped classroom model with Mind mapping media have higher learning outcomes compared to students who use the direct learning model with the discussion method.